(untitled) (Research, Society and Development, 2020)
The cachaça agribusiness is a representative practice in the Brazilian market. It is estimated that the sector produces 1.3 billion liters of beverage annually, and a total of 30,000 producing establishments generate more than 450.000 direct and indirect jobs. The cachaça production process is established in almost all Brazilian states, where the main producing states are São Paulo, Pernambuco, Ceará, Rio de Janeiro, Goiás and Minas Gerais, which account for about 75% of the national production. The cachaça production chain in the country is not homogeneous, in spite of the tradition and the economic importance of this beverage in the country. Improvements are sought in the development of technologies to improve and control the physicochemical and sensory aspects of the quality and standardization of the beverage. Thus, the objective of this work was to identify the similarity of the variables that determine the quality of cachaça produced in Brazil using multivariate cluster analysis. We collected 512 samples, and their physicochemical analyses were applied in multivariate analysis. Of the samples, 70% presented identity and quality standards required by the ABPM. All the results for the parameters analyzed were non-compliant with the legislation. With the PCA applied, a homogeneity in the production process with respect to the physicochemical profile was observed in the samples. In general, the production of cachaça can be inferred as being satisfactory, but much can be improved with respect to commercialization and standardization of Brazilian cachaça.